CESifo World Economic Survey August 2006 - Gernot Nerb; Anna Stangl (CESifo World Economic Survey, 2006)
World Economic Climate: World Economic Climate cools down somewhat - Economic Expectations: Assessments of the current economic situation improved again, but economic expectations downgraded - Inflation: Expectations edge up - Interest Rates: Stronger increase at the short than at the long end - Currencies: Japanese yen still seen as somewhat undervalued - Special Topic: Who should govern the Internet?
Keywords: 330